A dynamically reconfigurable electrochemical conversion material for high potential operating conditions and a method of preparation and use thereof

CN123018002APending Publication Date: 2026-10-30HENAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611090877.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但现代工业级能源转换器件实际服役过程中,长期处于高电流密度、高电位、活性氧(ROS)持续冲击的极端工况,极易引发催化剂Fe-NX配位键断裂,进而造成铁原子脱金属流失,最终诱发活性位点不可逆失活,催化性能持续衰减,极大限制催化剂的长效服役能力

Benefits of technology

[0033]1.本发明首创承载储备Fe的基底功能分区、负载FeN3-SnN4异核双原子主活性位点与低配位储备Sn的外侧功能分区协同构建的分区型氮碳复合结构,区别于常规金属简单共掺杂材料,实现两类储备金属分工协同作用,其中基底分区内低配位储备Fe为可封存、可调用修复单元,负责主活性Fe位点脱金属失活后定向补位重构FeN3-SnN4异核位点,直接恢复催化活性位点;外侧分区低配位储备Sn作为微环境维护单元,稳定SnN4电子调控底座并持续抑制ROS累积,分别完成活性恢复与催化微环境长效维护双重功能。厚度2~5nm的PDA衍生碳层及聚多巴胺包覆层承担跨分区碳氮源与金属螯合平台作用,二次热解作为分区结构锁定步骤,实现基底分区储备金属与外侧分区活性位点空间隔离,彻底打破单一储备原子无法同步兼顾活性再生与结构防护的技术局限,构建服役缺陷驱动的动态自修复催化体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018002A_ABST
    Figure CN123018002A_ABST
Patent Text Reader

Abstract

The application discloses a kind of dynamic reconfiguration electrochemical conversion material for high potential working condition and its preparation method and application, and electrochemical conversion material is partition type nitrogen-carbon composite structure, ZIF-8 derived nitrogen-doped porous carbon carrier is loaded FeN3-SnN4 heteronuclear diatomic main active site, low coordination reserve Fe and low coordination reserve Sn, low coordination reserve Fe is sealed in the interior of carbon carrier, for Fe main site deactivation after position reconstruction FeN3-SnN4 heteronuclear diatomic main active site, low coordination reserve Sn is distributed in the outside of carbon carrier, for maintaining Sn electronic regulation and active oxygen inhibition function, both synergies realize the in-situ self-repair of electrochemical conversion material catalytic active site.The initial ORR activity of electrochemical conversion material of the application is high, and long-term cycle stability is significantly improved under high current density, and it is suitable for zinc-air battery, fuel cell cathode catalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a dynamic reconfiguration electrochemical conversion material for high-potential operating conditions, its preparation method, and its application. Background Technology

[0002] The performance of energy conversion devices such as fuel cells and metal-air batteries highly depends on efficient and stable oxygen reduction (ORR) catalysts. Among them, Fe-NC-based single / dual-atom catalysts are promising alternatives to precious metal catalysts due to their low cost and excellent intrinsic activity. However, in actual service, modern industrial-grade energy conversion devices are subjected to extreme conditions of high current density, high potential, and continuous reactive oxygen species (ROS), which can easily lead to Fe-N oxidation of the catalyst. X The breaking of coordination bonds leads to the loss of iron atoms through demetallization, which ultimately induces irreversible deactivation of active sites, resulting in a continuous decline in catalytic performance and greatly limiting the long-term service life of the catalyst.

[0003] The failure of this type of catalyst is not a single process, but a chain of progressive positive feedback loops. First, the continuous attack of high potential and ROS weakens Fe-N. X Coordination bonds, and the loss of iron atoms after desorption, leave defects on the carbon support. Furthermore, these defects further catalyze the generation of more reactive oxygen species, continuously eroding the carbon framework and exacerbating structural damage, thus cyclically destroying the catalytic sites. Existing modification methods, such as enhanced metal coordination, carbon layer coating, and heteroatom doping, can only statically delay degradation and cannot achieve in-situ regeneration of deactivated catalytic sites. In addition, a few self-healing systems require external reagents and artificial triggering, making them unsuitable for the high current density, high potential, and continuous ROS impact of continuous cathodes in energy conversion devices.

[0004] If low-coordinated iron is directly introduced as a repair reserve, free iron atoms are prone to migration and aggregation, which can also induce Fenton side reactions and exacerbate ROS generation, failing to solve the long-term stability problem. Addressing the technical difficulties of existing technologies that only offer passive protection and lack in-situ dynamic repair mechanisms, this invention proposes a novel dual-reserve synergistic self-repair approach: Fe as the primary repair reserve and Sn as the auxiliary maintenance reserve. Relying on the dynamic active catalytic site reconstruction mechanism, it fundamentally breaks the failure chain of "coordination weakening - demetallization - defect-induced side reactions - framework erosion," thereby overcoming the bottleneck of long-term stability of Fe-NC catalysts. Currently, there are no related reports in this area. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a dynamically reconfigurable electrochemical conversion material for high-potential operating conditions and its preparation method. This electrochemical conversion material can achieve self-repair of active catalytic sites, self-stabilization of structure and long-term maintenance of catalytic performance under high current density, and can be used as a catalytic material for cathodes of energy conversion devices such as zinc-air batteries and fuel cells.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] The first aspect of this invention provides a dynamically reconfigurable electrochemical conversion material for high-potential operating conditions, which serves as a catalyst system with the core protective product. The electrochemical conversion material has a partitioned nitrogen-carbon composite structure, wherein a ZIF-8 derived nitrogen-doped porous carbon support is loaded with FeN3-SnN4 heteronuclear diatomic main active sites, low-coordination reserve Fe, and low-coordination reserve Sn. Its specific structural composition and functional mechanism are as follows:

[0008] Support framework: ZIF-8 derived nitrogen-doped porous carbon support, with high specific surface area, abundant carbon defects and nitrogen anchoring sites;

[0009] The composition and molar percentage of multi-level metal sites loaded on the carrier framework:

[0010] FeN3-SnN4 heteronuclear diatomic main active site: molar percentage of 60mol%~70mol%, as the core active unit for catalytic oxygen reduction reaction, relying on the synergistic enhancement of intrinsic catalytic activity by Fe and Sn bimetallic dp orbitals;

[0011] Low-coordination reserve Fe: with a molar percentage of 10 mol%~20 mol%, serves as the main repair unit. This low-coordination reserve Fe is encapsulated inside a ZIF-8-derived nitrogen-doped porous carbon support. After the FeN3 coordination bond breaks and iron atoms are demetallized and lost, the FeN3-SnN4 heteronuclear diatomic main active site is reconstructed and restored to catalytic activity by relying on the local electrochemical driving force induced by the defects of the ZIF-8-derived nitrogen-doped porous carbon support to migrate and fill the gap.

[0012] Low-coordination reserve Sn: with a molar percentage of 10 mol%~20 mol%, serves as an auxiliary maintenance unit. This low-coordination reserve Sn is distributed outside the ZIF-8 derived nitrogen-doped porous carbon support to continuously stabilize the SnN4 electronically regulated substrate, optimize the oxygen adsorption pathway, suppress the generation and accumulation of reactive oxygen intermediates throughout the process, and prevent the metal coordination bonds of the ZIF-8 derived nitrogen-doped porous carbon support and FeN3-SnN4 heteronuclear diatomic main active site from being corroded by reactive oxygen, thus preventing secondary damage to the catalytic active site.

[0013] Synergistic self-repair mechanism: Low-coordination reserve Fe targets and replenishes to regenerate deactivated catalytic active sites, while low-coordination reserve Sn synchronously regulates the electronic environment and blocks reactive oxygen erosion pathways. The two work together in a hierarchical manner to construct a dynamically reconfigurable catalytic system, which is used to achieve in-situ self-repair of catalytic active sites in electrochemical conversion materials. This effectively solves the technical bottleneck of irreversible catalytic activity decay and poor long-term stability of traditional Fe-NC catalysts under high current density.

[0014] The second aspect of this invention provides a method for preparing the above-mentioned dynamically reconfigurable electrochemical conversion material for high-potential operating conditions. This method employs a dopamine-coating-secondary pyrolysis partitioned nitrogen-carbon synthesis strategy, coupled with a dicyandiamide gradient nitrogen supplementation control method. It includes core steps S1 to S5, and the key process parameters and material ratios for each step are limited as follows:

[0015] Step S1: Dissolve zinc nitrate hexahydrate and ferrous sulfate heptahydrate in methanol and sonicate them. Then mix them with a methanol solution containing dimethylimidazole and continue sonicating. Place the mixture in a constant temperature oven and let it stand. Then centrifuge and vacuum dry to obtain the Fe-ZIF-8 precursor with high Fe doping content.

[0016] Step S2: Mix the high Fe-doped Fe-ZIF-8 precursor obtained in step S1 with dicyandiamide solid powder evenly and heat it to 900~1100℃ for a high-temperature pyrolysis to form Fe@NC powder with tiny Fe nanoclusters, Fe3C or / and FeOx nanodomains wrapped by nitrogen-doped carbon.

[0017] Step S3: Disperse the Fe@NC powder obtained in step S2 in a weakly alkaline Tris-HCl solution, and then add dopamine monomer to carry out a spontaneous oxidation polymerization reaction to form a polydopamine (PDA) coating layer with a thickness of 2~5nm on the surface of Fe@NC particles to obtain Fe@NC@PDA;

[0018] Step S4: The Fe@NC@PDA obtained in step S3 is immersed in a mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate, and stirred at room temperature to allow Fe and Sn ions to be uniformly chelated into the polydopamine coating layer of Fe@NC@PDA.

[0019] Step S5: The material impregnated in step S4 is placed in a tube furnace and heated to 700~900℃ for secondary high-temperature pyrolysis. During this process, the polydopamine coating layer is carbonized into a defect-rich NC support, and the surface Fe and Sn are reduced in situ and anchored to form FeN3-SnN4 heteronuclear diatomic main active sites. The internal Fe clusters are protected by the carbon layer and kept in a reserve state to obtain the target product FeSn-NC catalyst.

[0020] Further specifying, in step S1, the feeding ratio of zinc nitrate hexahydrate, ferrous sulfate heptahydrate, dimethylimidazole and methanol is 16~20mmol:0.3mmol:70~80mmol:300~400mL; the temperature of the constant temperature oven is 30~40℃, and the standing time in the constant temperature oven is 10~15h; the centrifugation conditions are 7000~9000rpm for 2~5min; washing with methanol 2~4 times, and vacuum drying at 50~70℃ for 10~15h.

[0021] Further specifying, in step S2, the mass ratio of the high Fe doping Fe-ZIF-8 precursor to dicyandiamide solid powder is 1:0.7~0.9; the high Fe doping Fe-ZIF-8 precursor and dicyandiamide solid powder are mixed evenly and loaded into a quartz magnetic boat, then placed in a tube furnace, heated to 1000℃ at a heating rate of 8~12℃ / min under high-purity N2 protection, held for 1~3h, and then naturally cooled to obtain Fe@NC powder, wherein the flow rate of high-purity N2 is 40~60sccm.

[0022] Further specifying, in step S3, the feeding ratio of Fe@NC powder, weakly alkaline Tris-HCl solution and dopamine monomer is 200mg:80~120mL:80~120mg, the molar concentration of the weakly alkaline Tris-HCl solution is 10mM, and the pH is 8.5; the reaction conditions for the spontaneous oxidation polymerization reaction are: stirring at 30~50℃ and atmospheric pressure at 100~300rpm for 6~10h, centrifugation at 8000~10000rpm for 4~6min, washing with deionized water and ethanol 2~4 times each, and vacuum drying at 50~70℃ for 10~15h. By setting the reaction conditions for the spontaneous oxidation polymerization reaction, it is ensured that a partitioned carbon isolation layer with a thickness of 2~5nm, i.e., a polydopamine coating layer, is formed.

[0023] Further specifying, the feeding ratio of Fe@NC@PDA to the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate in step S4 is 200mg:80~120mL, and the concentration of ferrous sulfate heptahydrate in the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate is 0.8~1.2mmol / L and the concentration of stannous sulfate is 0.4~0.6mmol / L; the impregnation process specifically involves adding Fe@NC@PDA to the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate, stirring at room temperature for 10~15h to allow the metal ions to be uniformly chelated in the polydopamine coating layer, centrifuging at 7000~9000rpm for 2~5min, washing with methanol 2~4 times, and vacuum drying at 50~70℃ for 10~15h.

[0024] Further specified, the temperature of the secondary high-temperature pyrolysis in step S5 is 800℃, the heating rate of the secondary high-temperature pyrolysis is 4~6℃ / min, the holding time is 1~3h, the protective atmosphere is high-purity N2, and the flow rate of the high-purity N2 is 40~60sccm.

[0025] The third aspect of this invention provides a method for evaluating the accelerated degradation stability of the above-mentioned electrochemical conversion materials and the ROS generation and inhibition behavior during the ORR reaction, used to verify the dual-reserve synergistic in-situ self-healing performance of the electrochemical conversion materials:

[0026] Electrochemical conversion materials were formulated into electrode slurries and subjected to accelerated cyclic voltammetry aging tests at a high scan rate of 200 mV / s in 0.1 M KOH alkaline electrolyte and 0.5 M H2SO4 acidic electrolyte, respectively. During long-cycle testing, defects on the electrode surface triggered local electrochemical driving effects, initiating the migration and reorganization of FeN3-SnN4 heteronuclear diatomic main active sites by low-coordination reserve Fe in the carbon substrate. At the same time, the low-coordination reserve Sn in the surface functional region continued to play an auxiliary maintenance role in electronic regulation and ROS inhibition, completing the in-situ self-repair of the FeN3-SnN4 heteronuclear diatomic main active sites. The test was set with gradient cycling cycles of 5000, 10000, and 20000 cycles. The long-term stability of the catalyst was evaluated by tracking the changes in half-wave potential and limiting current density under different cycle numbers.

[0027] In-situ infrared spectroscopy was used to compare the ROS evolution behavior of the catalysts prepared in Example 1 and Comparative Examples 1-4 during the ORR process. The results showed that the catalyst prepared in Example 1, thanks to the synergistic effect of the FeN3-SnN4 heteronuclear diatomic main active site and the electronic regulation of the Fe and Sn dual-reserve structures, significantly suppressed the generation and accumulation of reactive oxygen species intermediates throughout the process, and the ROS characteristic signal remained stable at a low value. The catalysts prepared in Comparative Examples 1-4, lacking the Sn electronic regulation substrate and the dual-reserve synergistic protection, were unable to block ORR side reactions, and ROS continuously accumulated as the reaction continued, resulting in a continuously increasing signal. Excessive ROS can damage the ZIF-8 derived nitrogen-doped porous carbon support and metal coordination structure, causing the loss of catalytic active sites and rapid degradation of catalytic performance. This characterization, from the perspective of intermediate evolution and interface protection mechanisms, confirms that the dual-reserve synergistic self-healing structure in the electrochemical conversion material prepared in this invention can effectively inhibit ROS corrosion and significantly improve the long-term stability of the catalyst.

[0028] The fourth aspect of this invention provides applications of the above-mentioned electrochemical conversion material, limiting its use as an oxygen reduction cathode catalyst material in energy conversion devices, specifically including two types of application scenarios:

[0029] The cathode catalytic material for a metal-air battery is preferably a zinc-air battery cathode catalytic material.

[0030] Cathode catalytic material for proton exchange membrane fuel cells.

[0031] The electrochemical conversion material exhibits a half-wave potential of 0.88V in an alkaline 0.1M KOH system and 0.825V in an acidic 0.5M H2SO4 system, demonstrating both excellent initial ORR activity and long-term self-healing stability. It can replace precious metal Pt / C catalysts and has the potential for large-scale industrial application.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] 1. This invention is the first to construct a partitioned nitrogen-carbon composite structure, which is a functional partitioned substrate supporting Fe, a main active site loaded with FeN3-SnN4 heteronuclear diatomic sites, and an outer functional partitioned low-coordination Sn. Unlike conventional simple co-doped metal materials, this invention achieves the division of labor and synergistic effect of the two types of reserve metals. The low-coordination Fe in the substrate partition is a resealable and retrievable repair unit, responsible for the directional replacement and reconstruction of FeN3-SnN4 heteronuclear sites after the main active Fe sites are demetallized and deactivated, directly restoring the catalytic active sites. The low-coordination Sn in the outer partition serves as a microenvironment maintenance unit, stabilizing the SnN4 electronic regulation base and continuously inhibiting ROS accumulation, thus completing the dual functions of activity restoration and long-term maintenance of the catalytic microenvironment. The PDA-derived carbon layer and polydopamine coating layer with a thickness of 2-5 nm serve as a cross-regional carbon and nitrogen source and metal chelation platform. Secondary pyrolysis acts as a regional structure locking step, realizing spatial isolation between the substrate regional metal storage and the outer regional active sites. This completely breaks the technical limitation that a single storage atom cannot simultaneously take into account both activity regeneration and structural protection, and constructs a dynamic self-healing catalytic system driven by service defects.

[0034] 2. Addressing the inherent industry bias that low-coordinated reserve Fe is prone to aggregation and induces Fenton side reactions that damage the carbon support, this invention achieves synergistic effects through the electronic regulation of low-coordinated reserve Sn. As a p-block metal, low-coordinated reserve Sn can undergo dp orbital charge delocalization transfer with the carbon framework and neighboring sites, reshaping the local electronic structure of the catalyst. On one hand, this lowers the oxygen reduction reaction energy barrier, driving the reaction towards a highly efficient four-electron pathway and reducing the generation of the Fenton reaction substrate H2O2 from the source. On the other hand, it constructs an electron-rich confined microenvironment, rapidly capturing and dissociating OO intermediates, forming an electronic protective wall around the low-coordinated reserve Fe, cutting off the supply channel of oxidant for the Fenton reaction. In-situ infrared spectroscopy confirms that low-coordinated reserve Sn can strengthen the bonding strength between the material and OO intermediates, suppressing ROS signal levels over a long period. This allows the low-coordinated reserve Fe, which is prone to side reactions, to safely and stably exert its in-situ repair capabilities. Even after long-term accelerated cycling, the activity decay is minimal, with slight performance recovery in some regions, demonstrating long-term stability far exceeding that of existing Fe-based catalysts.

[0035] 3. The entire process chain of this invention utilizes four synergistic steps: dicyandiamide, dopamine coating, Fe / Sn surface chelation, and secondary high-temperature pyrolysis. Each step functions independently and progressively completes the precise construction of the partitioned structure. Dicyandiamide does not simply increase the total nitrogen content of the carbon support; rather, it constructs a nitrogen-gradient functional partitioned carbon substrate through a single high-temperature pyrolysis. This relies on numerous nitrogen defects to anchor and coordinate embedded Fe clusters, Fe3C, and FeOx, maintaining Fe as a low-activity reserve phase at room temperature and suppressing metal aggregation and Fenton side reactions. Simultaneously, it enhances the interfacial compatibility between this carbon partition and the PDA-modified layer, ensuring uniform chelation and loading of metal ions. The PDA layer, acting as a platform for uniform Fe and Sn ion chelation, solidifies the partitioned morphology of "internal Fe storage, surface host sites, and Sn reserve" during the secondary high-temperature pyrolysis, preventing metal cross-layer mixing at high temperatures. The entire process can stably control the main active sites and the molar ratio of the two types of reserve metals, solving the problems of uneven metal coordination and poor batch repeatability in traditional pyrolysis, and simultaneously improving ORR activity, self-healing ability and industrial compatibility in acid and alkali media.

[0036] 4. This invention utilizes a 2-5 nm thick, cross-regional carbon isolation layer, namely a polydopamine coating layer, to achieve normal physical isolation of low-coordination stored Fe, enabling the low-coordination stored Fe to possess both controllable storage and on-demand retrieval characteristics, thus perfecting a dual-storage synergistic long-term protection system. Under normal conditions, the carbon isolation layer blocks the electrolyte and active oxygen, keeping the stored Fe in the carbon substrate region in a low-activity "dead state," inhibiting metal aggregation and Fenton corrosion. After long-cycle electrochemical cycling induces FeN3 coordination breakage, Fe loss, and the generation of interfacial defect gradients, the electrochemical driving force promotes the directional migration of low-coordination Fe stored in the carbon substrate region to the surface functional area, where it re-coordinates with surface carbon and nitrogen defects, reconstructing the FeN3-SnN4 heteronuclear diatomic main active sites in situ, and reversibly restoring the half-wave potential and limiting current density. By combining low-coordination Sn reserves to continuously regulate the electronic environment and block ROS erosion, a dual long-term protection is formed by "reserved Fe repair sites and reserved Sn protective microenvironment". Excellent half-wave potentials of 0.88V and 0.825V are achieved in 0.1M KOH and 0.5M H2SO4 electrolytes, respectively. After accelerated aging at a high scan rate of 200mV / s for 20,000 cycles, the performance degradation is much lower than that of control samples without reserves and with single reserves.

[0037] 5. This invention relies on the synergistic regulation of multiple pyrolysis parameters and the non-equilibrium kinetic freezing effect to precisely and controllably prepare catalytic materials with uniform functional partitions, stably achieving the optimal ratio of 60mol%~70mol% FeN3-SnN4 heteronuclear diatomic main active sites, 10mol%~20mol% low-coordination reserve Fe, and 10mol%~20mol% low-coordination reserve Sn. The gradient nitrogen-carbon substrate partition and the PDA-derived nitrogen-carbon surface partition form a spatial separation barrier, naturally preventing the disordered mixing of reserve metals and main active sites. Multi-level carbon defects simultaneously serve as the endogenous driving force for the directional migration and reconstruction of low-coordination reserve Fe, ensuring the orderly progress of the self-repair process. Traditional catalysts rely solely on static coordination enhancement and surface coating to passively delay performance degradation, failing to address the problem of irreversible site damage. This invention upgrades the catalyst design concept to a dynamic self-repair system that is damage-prone, retrievable, and reconfigurable, transforming defects and potential gradients generated during service into self-repair driving forces. This dynamic catalytic design paradigm provides a new approach for the development of various long-term stable electrocatalytic materials, possessing outstanding academic innovation value and engineering application prospects. Attached Figure Description

[0038] Figure 1 X-ray powder diffraction patterns of the catalysts prepared in Example 1 and Comparative Examples 1-4.

[0039] Figure 2 In the image, a, b, c, d, and e are scanning electron microscope images of the catalysts prepared in Example 1 and Comparative Examples 1-4, respectively.

[0040] Figure 3 In Figure a, the linear voltammetric scan curves of the catalysts prepared in Example 1 and Comparative Examples 1-4 at 1600 rpm in 0.1 M KOH solution are shown. Figure 3 Figure b shows the linear voltammetric scan curves of the catalysts prepared in Example 1 and Comparative Examples 1-4 in 0.5M H2SO4 solution at 900 rpm. Figure 3 c and d represent the performance changes of the catalyst prepared in Example 1 during accelerated durability testing, with a scan rate of 200 mV / s and continuous cycles of 5000, 10000, and 20000 cycles, respectively.

[0041] Figures 4-5 In Tables a, b, c, and d, the catalysts prepared in Comparative Examples 1-4 exhibit performance changes during accelerated durability testing, respectively. Through comparison, it was found that the catalyst prepared in Example 1 relies on the targeted replacement and reconstruction of FeN3-SnN4 heteronuclear diatomic main active sites by low-coordination reserve Fe. At the same time, the low-coordination reserve Sn continuously maintains electronic regulation and catalytic microenvironment stability, and the catalyst activity can gradually stabilize and exhibit a slight recovery characteristic. Its long-term service performance is significantly better than that of the catalysts prepared in Comparative Examples 1-4 (as shown in Tables 1 and 2).

[0042] Figures 6-10 show the in-situ infrared spectra of the catalysts prepared in Example 1 and Comparative Examples 1-4 before and after stability testing. Spectral analysis reveals that, compared to the samples prepared in Comparative Examples 1-4, the catalyst prepared in Example 1 effectively inhibits the formation of reactive oxygen species (ROS). The spectra only detected *OH and *OO adsorption intermediates, without observing the characteristic absorption peak of *OOH. After long-term stability testing, the infrared characteristic peak of the *OO intermediate corresponding to the catalyst prepared in Example 1 showed a significant blue shift (as shown in Table 3). Based on the infrared shift pattern, this blue shift phenomenon confirms that the introduction of low-coordination reserve Sn enhances the adsorption between the catalyst and the *OO intermediate, strengthening the chemical bond strength of the intermediate. Conversely, the in-situ infrared spectra of the four groups of catalysts prepared in Comparative Examples 1-4 before and after stability testing did not show the significant evolutionary pattern of ROS inhibition observed in the catalyst prepared in Example 1, indicating difficulty in effectively controlling reactive oxygen species. Detailed Implementation

[0043] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments, but this should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments are commercially available unless otherwise specified.

[0044] Example 1

[0045] Step S1: Preparation of Fe-ZIF-8 precursor: Dissolve 18 mmol zinc nitrate hexahydrate and 0.3 mmol ferrous sulfate heptahydrate in 150 mL methanol, sonicate for 10 min, mix with 150 mL methanol solution containing 75 mmol dimethylimidazole, sonicate for another 10 min, place in a constant temperature oven and let stand at 35 °C for 12 h; centrifuge at 8000 rpm for 3 min, wash twice with methanol, and vacuum dry at 60 °C for 12 h to obtain Fe-ZIF-8 precursor;

[0046] Step S2: High-temperature pyrolysis: Take 1g of Fe-ZIF-8 precursor and 0.8g of dicyandiamide solid powder and mix them thoroughly and evenly. Put the mixture into a quartz magnetic boat and place it in a tube furnace. Under the protection of high-purity N2 (flow rate 50sccm), heat it to 1000℃ at a heating rate of 10℃ / min and hold it for 1h. After natural cooling, Fe@NC is obtained.

[0047] Step S3: Dopamine coating: 200 mg Fe@NC was dispersed in 100 mL of 10 mM Tris-HCl (pH=8.5) solution, sonicated for 30 min, and then 100 mg of dopamine monomer was added. The mixture was stirred at 40 °C and atmospheric pressure at a low speed of 200 rpm for 8 h, centrifuged at 9000 rpm for 5 min, washed 3 times each with deionized water and ethanol, and vacuum dried at 60 °C for 12 h to obtain Fe@NC@PDA.

[0048] Step S4: Metal impregnation: Immerse 200 mg Fe@NC@PDA in 100 mL of a mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate (the concentration of ferrous sulfate heptahydrate is 1.0 mmol / L (27.8 mg) and the concentration of stannous sulfate is 0.5 mmol / L (10.7 mg)). Stir at room temperature for 12 h to allow metal ions to be uniformly chelated on the surface of PDA. Centrifuge at 8000 rpm for 3 min, wash twice with methanol, and vacuum dry at 60 °C for 12 h.

[0049] Step S5: Secondary high-temperature pyrolysis: The dried material is placed in a tube furnace and heated to 800℃ at a heating rate of 5℃ / min under the protection of high-purity N2 (flow rate 50 sccm) and held for 2 hours. After natural cooling, the target dual-reserve FeSn-NC catalyst is obtained.

[0050] Comparative Example 1 (lacking core iron reserve units and low-coordination tin reserve unit partitioning structure)

[0051] Step S1: Prepare two 500mL beakers, named beaker A and beaker B respectively. Accurately weigh 18mmol of zinc nitrate hexahydrate into beaker A, add 150mL of methanol, and then sonicate in an ultrasonic machine for 10min. Accurately weigh 75mmol of dimethylimidazole into beaker B, add 150mL of methanol, and then sonicate in an ultrasonic machine for 10min. Pour the solution from beaker B into beaker A, and continue sonicating for another 10min. Seal beaker A with plastic wrap and place it in a constant temperature incubator at 35℃ for 12h. Centrifuge at 8500rpm for 3min, wash twice with methanol, and vacuum dry at 60℃ for 12h to obtain the metal-free ZIF-8 precursor.

[0052] Step S2: Weigh 1g of ZIF-8 precursor and 1.2g of dicyandiamide, mix them evenly and place them in a quartz ceramic boat, transfer them to a tube furnace, and pass high-purity N2 through it for protection. The flow rate of high-purity N2 is 50 sccm. Then heat it to 1000℃ at a heating rate of 10℃ / min and hold it for 1h. After natural cooling, the NC material is obtained.

[0053] Step S3: Accurately weigh 100 mg of the NC material obtained in step S2, 11.2 g of FeSO4·7H2O and 8.5 g of stannous sulfate and add them to the ball mill. Perform mechanical and physical grinding for 20 min, controlling the pressure at around 8 MPa.

[0054] Step S4: The material obtained after grinding was placed in a tube furnace and subjected to secondary high-temperature pyrolysis under the protection of high-purity N2. The flow rate of high-purity N2 was 50 sccm, and the heating rate was 5℃ / min. A heating stage (from 50℃ to 900℃ for 170 min), an isothermal stage (maintained at 900℃ for 120 min), and a cooling stage (from 900℃ to room temperature) were set to obtain a FeSn-NC catalyst without reserves.

[0055] Comparative Example 2 (only has tin reserves, lacks iron reserves for replenishment)

[0056] Step S1: Prepare two 500mL beakers, named Beaker A and Beaker B respectively. Accurately weigh 18mmol zinc nitrate hexahydrate and 0.2mmol stannous sulfate into Beaker A, add 150mL methanol, and then sonicate in an ultrasonic machine for 10min. Accurately weigh 75mmol dimethylimidazole into Beaker B, add 150mL methanol, and then sonicate in an ultrasonic machine for 10min. Pour the solution from Beaker B into Beaker A, and continue sonicating for another 10min. Seal Beaker A with plastic wrap and place it in a constant temperature incubator at 35℃ for 12h. Centrifuge at 8500rpm for 3min, wash twice with methanol, and vacuum dry at 60℃ for 12h to obtain the Sn-ZIF-8 precursor.

[0057] Step S2: Weigh 1g of Sn-ZIF-8 precursor and 0.8g of dicyandiamide, mix thoroughly, transfer to a quartz magnetic boat, place in a tube furnace, and purge with high-purity N2 at a flow rate of 50 sccm. Then heat to 650℃ at a heating rate of 10℃ / min and hold for 1 hour. Allow to cool naturally to obtain Sn-N x Material.

[0058] Step S3: Weigh 100 mg of Sn-Nx material obtained in step S2, 14 mg of FeSO4·7H2O and 10.7 mg of SnSO4 and add them to a ball mill. Perform mechanical and physical grinding for 20 minutes, controlling the pressure at about 8 MPa.

[0059] Step S4: Transfer the ground sample to a quartz magnetic boat and place it in a tube furnace. High-purity N2 is introduced into the tube furnace for protection at a flow rate of 50 sccm. The temperature is increased in steps at a rate of 5℃ / min: 700℃ for 30 min → 800℃ for 30 min → 950℃ for 60 min. After natural cooling, only Sn catalyst is obtained.

[0060] Comparative Example 3 (only has iron storage, lacks tin storage and microenvironment maintenance functions)

[0061] Step S1: Prepare two 500mL beakers, named Beaker A and Beaker B respectively. Accurately weigh 18mmol zinc nitrate hexahydrate and 0.3mmol ferrous sulfate heptahydrate into Beaker A, add 150mL methanol, and then sonicate in an ultrasonic machine for 10min. Accurately weigh 75mmol dimethylimidazole into Beaker B, add 150mL methanol, and then sonicate in an ultrasonic machine for 10min. Pour the solution from Beaker B into Beaker A, and continue sonicating for another 10min. Seal Beaker A with plastic wrap and place it in a constant temperature incubator at 35℃ for 12h. Centrifuge at 8500rpm for 3min, wash twice with methanol, and vacuum dry at 60℃ for 12h to obtain the Fe-ZIF-8 precursor.

[0062] Step S2: Weigh 1g of Fe-ZIF-8 precursor and 0.8g of dicyandiamide, mix thoroughly, transfer to a quartz magnetic boat, place in a tube furnace, and purge with high-purity N2 at a flow rate of 50 sccm. Then heat to 650℃ at a heating rate of 10℃ / min and hold for 1 hour. Allow to cool naturally to obtain Fe-N x Material.

[0063] Step S3: Weigh 100 mg of Fe-Nx material, 14 mg of FeSO4·7H2O and 10.7 mg of SnSO4 obtained in step S2 and add them to a ball mill. Perform mechanical and physical grinding for 20 minutes, controlling the pressure at around 8 MPa.

[0064] Step S4: Transfer the ground sample to a quartz magnetic boat and place it in a tube furnace. Under the protection of high-purity N2 (flow rate 50 sccm), the temperature is increased in steps at a rate of 5℃ / min: 700℃ for 30 min → 800℃ for 30 min → 950℃ for 60 min. After natural cooling, only Fe catalyst is obtained.

[0065] Comparative Example 4 (without dicyandiamide, to verify the stabilizing effect of nitrogen gradient and stored iron).

[0066] Step S1: Preparation of Fe-ZIF-8 precursor: Dissolve 18 mmol zinc nitrate hexahydrate and 0.3 mmol ferrous sulfate heptahydrate in 150 mL methanol, sonicate for 10 min, mix with 150 mL methanol solution containing 75 mmol dimethylimidazole, sonicate for another 10 min, place in a constant temperature oven and let stand at 35 °C for 12 h; centrifuge at 8000 rpm for 3 min, wash twice with methanol, and vacuum dry at 60 °C for 12 h to obtain Fe-ZIF-8 precursor;

[0067] Step S2: High-temperature pyrolysis: Take 1g of Fe-ZIF-8 precursor, put it into a quartz magnetic boat, place it in a tube furnace, and heat it to 1000℃ at a heating rate of 10℃ / min under the protection of high-purity N2 (flow rate 50sccm) and hold it for 1h. After natural cooling, Fe@NC is obtained.

[0068] Step S3: Dopamine coating: 200 mg Fe@NC was dispersed in 100 mL of 10 mM Tris-HCl (pH=8.5) solution, sonicated for 30 min, and then 100 mg of dopamine monomer was added. The mixture was stirred at 40 °C and atmospheric pressure at a low speed of 200 rpm for 8 h, centrifuged at 9000 rpm for 5 min, washed 3 times each with deionized water and ethanol, and vacuum dried at 60 °C for 12 h to obtain Fe@NC@PDA.

[0069] Step S4: Metal impregnation: Immerse 200 mg Fe@NC@PDA in 100 mL of a mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate (the concentration of ferrous sulfate heptahydrate is 1.0 mmol / L and the concentration of stannous sulfate is 0.5 mmol / L), stir at room temperature for 12 h to allow metal ions to be uniformly chelated on the surface of PDA, centrifuge at 8000 rpm for 3 min, wash twice with methanol, and vacuum dry at 60 °C for 12 h;

[0070] Step S5: Secondary high-temperature pyrolysis: The material obtained from the above drying is placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under the protection of high-purity N2 (flow rate 50 sccm) and held for 2 hours. After natural cooling, the dual-reserve FeSn-NC catalyst is obtained.

[0071] Comparative Example 5: 20 wt% Commercial Pt / C catalyst

[0072] Each comparative example abandons the refined synthesis logic of core-shell coating and adopts a simple preparation method of direct co-doping of metal and carbon matrix, mechanical grinding and mixing of powder, and single pyrolysis. Lacking the conditions of polydopamine layered anchoring and nitrogen-carbon matrix partitioning, it is difficult to achieve the partitioned and controllable synthesis of reserve metal and main active site. Therefore, only catalysts without reserves or with single-type reserves can be prepared. This kind of preparation process is simple to operate and the raw materials are easy to mix, which objectively allows various comparative examples to be successfully prepared.

[0073] Table 1. Catalyst stability tests of Examples and Comparative Examples 1-4 under alkaline conditions. 1 / 2 Attenuation and limiting current retention

[0074] Example 1 -10mV -7mV +4mV 96.8% Comparative Example 1 -15mV -22mV -10mV 92.0% Comparative Example 2 -19mV -8mV -15mV 91.0% Comparative Example 3 -25mV -10mV -8mV 88.3% Comparative Example 4 -27mV -15mV -9mV 85.6%

[0075] Table 2 Catalyst stability tests of Examples and Comparative Examples 1-4 under acidic conditions. 1 / 2 Attenuation and limiting current retention

[0076] Example 1 -10mV -10mV +6mV 91.6% Comparative Example 1 -23mV -17mV -10mV 91.7% Comparative Example 2 -29mV -9mV -6mV 90.3% Comparative Example 3 -26mV -17mV -10mV 89.3% Comparative Example 4 -60mV -31mV -12mV 83.4%

[0077] Table 3. Differences in intensity and shift of in-situ infrared spectra of catalysts before and after stabilization in Examples 1-4 and Comparative Examples 1-4.

[0078] Example 1 Reduced by 28.6% Reduced by 27.1% / / Blue Shift Comparative Example 1 Reduced by 17.2% Reduced by 75.0% / Enhanced by 35.0% Redshift Comparative Example 2 Reduced by 35.2% / Reduced by 37.3% Reduced by 34.4% constant Comparative Example 3 Reduced by 38.1% / Reduced by 40.5% From 0 to 1 constant Comparative Example 4 Reduced by 67.3% Reduced by 69.2% / From 0 to 1 Redshift

[0079] The rechargeable zinc-air battery / fuel cell catalyst prepared in this invention exhibits excellent ORR catalytic activity. Figure 3 The electrical performance test results show that the FeSn-NC catalysts prepared in Example 1 of this invention all have large limiting current densities and half-wave potentials. By comparing the catalysts prepared in Example 1 with those prepared in Comparative Examples 1 to 4, it can be concluded that the FeSn-NC catalysts prepared in Example 1 have the best catalytic activity.

[0080] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Various changes and modifications can be made to the present invention without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A dynamically reconfigurable electrochemical conversion material for high-potential operating conditions, characterized in that: The electrochemical conversion material is a partitioned nitrogen-carbon composite structure, wherein the ZIF-8 derived nitrogen-doped porous carbon support is loaded with FeN3-SnN4 heteronuclear diatomic main active sites, low-coordination reserve Fe, and low-coordination reserve Sn. The low-coordination reserve Fe is encapsulated inside the ZIF-8 derived nitrogen-doped porous carbon support and is used to fill in and reconstruct the FeN3-SnN4 heteronuclear diatomic main active sites after the Fe host site is deactivated. The low-coordination reserve Sn is distributed outside the ZIF-8 derived nitrogen-doped porous carbon support and is used to maintain the electronic regulation and reactive oxygen species inhibition functions of Sn. The two work together to achieve in-situ self-repair of the catalytic active sites of the electrochemical conversion material.

2. The dynamically reconfigurable electrochemical conversion material for high-potential operating conditions according to claim 1, characterized in that: The FeN3-SnN4 heteronuclear diatomic main active site has a molar percentage of 60 mol%~70 mol%, serving as the core active unit for catalytic oxygen reduction reaction. It enhances intrinsic catalytic activity through the synergistic enhancement of Fe and Sn bimetallic dp orbitals. The low-coordination reserve Fe has a molar percentage of 10 mol%~20 mol%, serving as the main repair unit. After FeN3 coordination bond breakage and iron atom demetallization loss, it utilizes the local electrochemical driving force induced by defects in the ZIF-8 derived nitrogen-doped porous carbon support to directionally migrate and replenish the FeN3-SnN4 heteronuclear diatomic main active site, thus restoring catalytic activity. The low-coordination reserve Sn has a molar percentage of... The concentration is 10 mol%~20 mol%, which serves as an auxiliary maintenance unit to continuously stabilize the SnN4 electronically regulated substrate, optimize the oxygen adsorption pathway, suppress the generation and accumulation of reactive oxygen intermediates throughout the process, and prevent the metal coordination bonds of the ZIF-8 derived nitrogen-doped porous carbon support and FeN3-SnN4 heteronuclear diatomic main active sites from being corroded by reactive oxygen, thus preventing secondary damage to the catalytic active sites. The low-coordination reserve Fe is used for targeted replacement to regenerate deactivated catalytic active sites, and the low-coordination reserve Sn is used to simultaneously regulate the electronic environment and block the reactive oxygen erosion pathway. The two work together in a hierarchical manner to construct a dynamically reconfigurable catalytic system, which is used to achieve in-situ self-repair of the catalytic active sites of electrochemical conversion materials.

3. A method for preparing a dynamically reconfigurable electrochemical conversion material under high-potential operating conditions as described in claim 1 or 2, characterized in that... The specific preparation steps are as follows: Step S1: Dissolve zinc nitrate hexahydrate and ferrous sulfate heptahydrate in methanol and sonicate them. Then mix them with a methanol solution containing dimethylimidazole and continue sonicating. Place the mixture in a constant temperature oven and let it stand. Then centrifuge and vacuum dry to obtain the Fe-ZIF-8 precursor with high Fe doping content. Step S2: Mix the high Fe-doped Fe-ZIF-8 precursor obtained in step S1 with dicyandiamide solid powder evenly and heat it to 900~1100℃ for a high-temperature pyrolysis to form Fe@NC powder with tiny Fe nanoclusters, Fe3C or / and FeOx nanodomains wrapped by nitrogen-doped carbon. Step S3: Disperse the Fe@NC powder obtained in step S2 in a weakly alkaline Tris-HCl solution, then add dopamine monomer to carry out spontaneous oxidation polymerization, and form a polydopamine coating layer with a thickness of 2~5nm on the surface of Fe@NC particles to obtain Fe@NC@PDA; Step S4: The Fe@NC@PDA obtained in step S3 is immersed in a mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate, and stirred at room temperature to allow Fe and Sn ions to be uniformly chelated in the polydopamine coating layer of Fe@NC@PDA. Step S5: The material impregnated in step S4 is placed in a tube furnace and subjected to secondary pyrolysis at 700~900℃. During this process, the polydopamine coating layer is carbonized into a defect-rich NC support, and the surface Fe and Sn are reduced in situ and anchored to form FeN3-SnN4 heteronuclear diatomic main active sites. The internal Fe clusters are protected by the carbon layer and kept in a reserve state to obtain the target product FeSn-NC catalyst.

4. The preparation method of the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions according to claim 3, characterized in that: In step S1, the feeding ratio of zinc nitrate hexahydrate, ferrous sulfate heptahydrate, dimethylimidazole, and methanol is 16-20 mmol: 0.3 mmol: 70-80 mmol: 300-400 mL; the temperature of the constant temperature oven is 30-40℃, and the standing time in the constant temperature oven is 10-15 h; the centrifugation conditions are 7000-9000 rpm for 2-5 min; the product is washed with methanol 2-4 times and vacuum dried at 50-70℃ for 10-15 h.

5. The method for preparing the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions according to claim 3, characterized in that: In step S2, the mass ratio of the high Fe-doped Fe-ZIF-8 precursor to dicyandiamide solid powder is 1:0.7~0.

9. The high Fe-doped Fe-ZIF-8 precursor and dicyandiamide solid powder are mixed evenly and loaded into a quartz magnetic boat, which is then placed in a tube furnace. Under the protection of high-purity N2, the temperature is raised to 1000℃ at a heating rate of 8~12℃ / min and held for 1~3h. After natural cooling, Fe@NC powder is obtained, wherein the flow rate of high-purity N2 is 40~60sccm.

6. The method for preparing the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions according to claim 3, characterized in that: In step S3, the feeding ratio of Fe@NC powder, weakly alkaline Tris-HCl solution, and dopamine monomer is 200mg:80~120mL:80~120mg. The molar concentration of the weakly alkaline Tris-HCl solution is 10mM, and the pH is 8.

5. The reaction conditions for the spontaneous oxidation polymerization reaction are: stirring at 30~50℃ and atmospheric pressure at 100~300rpm for 6~10h, centrifuging at 8000~10000rpm for 4~6min, washing with deionized water and ethanol 2~4 times each, and vacuum drying at 50~70℃ for 10~15h. By setting the reaction conditions for the spontaneous oxidation polymerization reaction, a partitioned carbon isolation layer with a thickness of 2~5nm, i.e., a polydopamine coating layer, is formed.

7. The method for preparing the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions according to claim 3, characterized in that: In step S4, the feeding ratio of Fe@NC@PDA to the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate is 200 mg: 80~120 mL. The concentration of ferrous sulfate heptahydrate in the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate is 0.8~1.2 mmol / L, and the concentration of stannous sulfate is 0.4~0.6 mmol / L. The impregnation process is as follows: Fe@NC@PDA is added to the mixed methanol solution of ferrous sulfate heptahydrate and stannous sulfate, stirred at room temperature for 10~15 h to allow the metal ions to be uniformly chelated in the polydopamine coating layer, centrifuged at 7000~9000 rpm for 2~5 min, washed with methanol 2~4 times, and vacuum dried at 50~70℃ for 10~15 h.

8. The method for preparing the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions according to claim 3, characterized in that: The temperature of the secondary high-temperature pyrolysis in step S5 is 800℃, the heating rate of the secondary high-temperature pyrolysis is 4~6℃ / min, the holding time is 1~3h, the protective atmosphere is high-purity N2, and the flow rate of the high-purity N2 is 40~60sccm.

9. The application of the dynamically reconfigurable electrochemical conversion material under high-potential operating conditions as described in claim 1 or 2 as an oxygen reduction cathode catalyst material for energy conversion devices.

10. The application according to claim 9, characterized in that: The energy conversion device oxygen reduction cathode is either a metal-air battery oxygen reduction cathode or a proton exchange membrane fuel cell oxygen reduction cathode.